Chronological order exegesis “Bāyān alMa‘ānī” An Introduction to its Methodology, Approach & Pivotal Role in Tafsīr Literature - Dr. Muhammad Saeed Shaikh; Rizwan Rasheed (jihat-ul-islam, 2021)
This article briefly review the first complete chronological order exegesis Bāyān al-Ma‘ānī written by exegete Mullah ‘Abdul Qādir Ḥawaish. Qur’ān, an everlasting miracle and last message of Allah Almighty, revealed on Prophet Muḥammad (ﷺ) in 7th century CE. It contains injunctions and rulings to all facets of life. To provide elucidation for better understanding and conviction of Allah’s will is certainly the reason, different kinds of Qur’ānic commentaries are being penned from early Islāmic era to present time, constantly. Undoubtedly, Tafsīr is the genre that encompasses most volume of Islāmic intellectual heritage. Two arrangement orders of Qur’ānic chapters and verses are classified by Muslim ‘Ulamaā. Present order of Qur’ān arrangement is different from chronological order and arranged by Prophet Muḥammad (ﷺ) by the will of Allah Almighty under the wise counsel of Jibrā’ēl (علیہ السلام). Approximately, all exegeses of Qur’ān from classical era to modern time, has been written according to present arrangement. Bāyān al-Ma‘ānī is an Arabic chronological order modern exegesis written by ‘Irāqī Muslim academic, Mullah Ḥawaish (d. 1978 CE). However, as a consequence of, following descending orders of Qur’ān, this scholarly work is bit dissimilar to common exegeses. In this article, methodology, approach and divergent of this extraordinary exegesis as compare to standard traditional commentaries, has been discussed. Hitherto, research study indicate, it is a magnificent Tafsīr bil Māthūr, written in modern time, handy for general reader of intermediate level.